Globalization and heterogeneity: Evidence from Hollywood - Konrad Adler; Simon Fuchs (Federal Reserve Bank of Atlanta, 2022)
Linder (1961) conjectured that taste differences could impede trade flows. We extend Krugman (1980) to allow for producers that face taste heterogeneity with volatile demand. Consumers are characterized by different taste over product attributes and idiosyncratic risk. Firms face a portfolio type of problem where they trade off supplying the largest consumer groups against higher exposure to group-specific risk. We develop an empirical strategy to estimate consumer taste from observed market shares across multiple distinct markets of the same product, as well as the key parameters that pin down the firm's portfolio choice problem. We apply our framework to estimate the impact of the rise of China on the global movies market and characterize the heterogeneous welfare effects across countries.
Keywords: F11; F14; 330; taste heterogeneity; volatility; gains from trade